STRATEGI PENYIARAN RADIO METTA SOLO FM DALAM MEMPERTAHANKAN PENDENGAR GENERASI MILENIAL PADA PROGRAM CLUB 90’S - Febriani, Yesika Amanda; Riyanto, Buddy; Aji, Haryo Kusumo (Solidaritas, 2024)
This research discusses Radio Metta Solo Fm's Broadcasting Strategy in Retaining Millennial Generation Listeners on the Club 90's Program. This type of research is descriptive qualitative and analyzed using the theory of Programming Strategy by Susan Tyler Eastman. Data sources consist of primary data, namely interviews and observations, and secondary data, namely documentation. The results showed that (1) The compatibilty strategy is by determining the broadcast schedule with the daily activities carried out by the community. (2) Habit formation strategy by scheduling broadcast programs and having a special announcer so that listeners get used to the announcer's broadcast style. (3) Audience flow control strategies by presenting listener favorite songs and fulfilling listener requests, as well as conducting monitoring and evaluation. (4) The strategy of conserving program resources by saving and reusing a program that once existed but with a different format. (5) Breadth of appeal strategy by holding interviews with 90s artists and holding quizzes for listeners. Keywords: broadcasting strategy, radio, club 90's